1986
DOI: 10.1159/000167114
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Women with Chronic Renal Failure

Abstract: We describe 19 pregnancies in 18 women with chronic renal disease and plasma creatinine ≥1.6 mg/dl before pregnancy. There were 2 spontaneous abortions (11th and 21st week), 2 therapeutic abortions (18th and 19th week), 1 stillbirth (30th week), 1 neonatal death (31st week) and 13 live births, 7 of them were preterm. Nine cesarean sections were done. Serial determinations of plasma creatinine during pregnancy showed a trend to decrease during the first half and to increase during the second half of pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…These pregnancies are frequently associated with a progressive decline in renal function that may result in end-stage renal failure even in female patients whose serum creatinine are mildly elevated at the start of their pregnancy [4, 5, 6, 7]. For example, Jones and Hayslett [7]reported that the mean serum creatinine increased from 1.9 ± 0.8 mg/dl (168 ± 71 µmol/l) in the first trimester of pregnancy to 2.5 ± 1.3 mg/dl (221 ± 115 µmol/l) in third trimester (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These pregnancies are frequently associated with a progressive decline in renal function that may result in end-stage renal failure even in female patients whose serum creatinine are mildly elevated at the start of their pregnancy [4, 5, 6, 7]. For example, Jones and Hayslett [7]reported that the mean serum creatinine increased from 1.9 ± 0.8 mg/dl (168 ± 71 µmol/l) in the first trimester of pregnancy to 2.5 ± 1.3 mg/dl (221 ± 115 µmol/l) in third trimester (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although prospective data are not available, it is probable that strict control of hypertension during pregnancy would have protective effects on the kidney as has been demonstrated in nonpregnant women [15]. Birth weights and fetal survival rates are lower in pregnant hypertensive women than in pregnant normotensive women [4, 5, 6, 9, 16, 17, 18]. This emphasizes the importance of controlling blood pressure during pregnancy in order to preserve the maternal renal function and improve the fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have been specifically devoted to preg nancy in women with chronic renal failure [61][62][63]. They cumulatively include 81 pregnancies in 78 women with serum creatinine > 1 .4 mg/dl at conception (table 4).…”
Section: Chronic Renal Insufficiencymentioning
confidence: 99%
“…Therefore, pregnancy in patients with ANCA-associated glomerulonephritis is rare, and information regarding the management of ANCA-associated glomerulonephritis during pregnancy is limited. Moreover, pregnancy in patients with a low estimated glomerular filtration rate (eGFR) for any reason accelerates declines in the kidney function accompanied with a high rate of obstetrical complications (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%